Real-time, high-resolution imaging of tumor cells in genetically engineered and orthotopic models of thyroid cancer. Issue 10 (October 2020) - Shanja-Grabarz, Xhesika; Coste, Anouchka; Entenberg, David; Di Cristofano, Antonio
Abstract : Genetically engineered and orthotopic xenograft mouse models have been instrumental for increasing our understanding of thyroid cancer progression and for the development of novel therapeutic approaches in a setting that is more physiologically relevant than the classical subcutaneous flank implants. However, the anatomical location of the thyroid gland precludes a non-invasive analysis at the cellular level of the interactions between tumor cells and the surrounding microenvironment and does not allow a real-time evaluation of the response of tumor cells to drug treatments. As a consequence, such studies have generally only relied on endpoint approaches, limiting the amount and depth of the information that could be gathered. Here we describe the development of an innovative approach to imaging specific aspects of thyroid cancer biology, based on the implantation of a permanent, minimally invasive optical window that allows high-resolution, multi-day, intravital imaging of the behavior and cellular dynamics of thyroid tumors in the mouse. We show that this technology allows visualization of fluorescently tagged tumor cells both in immunocompetent, genetically engineered mouse models of anaplastic thyroid cancer (ATC) and in immunocompromised mice carrying orthotopic implanted human or mouse ATC cells. Furthermore, the use of recipient mice in which endothelial cells and macrophages are fluorescently labeled allows the detection of the spatial and functional relationship between tumor cells and their microenvironment. Finally, we show that ATC cells expressing a fluorescent biosensor for caspase 3 activity can be effectively utilized to evaluate, in real-time, the efficacy and kinetics of action of novel small molecule therapeutics. This novel approach to intravital imaging of thyroid cancer represents a platform that will allow, for the first time, the longitudinal, in situ analysis of tumor cell responses to therapy and of their interaction with the microenvironment.